Analisis Prediksi Kebangkrutan Perusahaan Sektor Pertambangan Dan Pertanian Menggunakan Metode Grover Tahun 2012-2015 - Limanto, Michael Citra (Fakultas Ekonomi Universitas Wisnuwardhana, 2017)
ABSTRACT. The agricultural sector and mining in Indonesia are a sector which most influential for Indonesia because the state is rich in will material of mining and also is a agraris. Overall according to the central bureau of statistics ( CBS ) in 2014 that the gross domestic product decline, GDP in 2013 only grow 5.6 percent compared with the in 2012 6 % and descending in 2014 about 5 %. A method of Grover is research methodology this is refinement of formula Altman and have research who wears a method of Altman. The purpose of this study is to find companies the mining sector and agriculture potentially bankrupt or not decline in the 2012-2015 measured by a method of Grover and he knows comparison the mining sector or agricultural have better bankrupt. Bankruptcy is a state of being or a situation in which company failed to or not able to meet obligations because firms experienced a lack of. The research is research quantitative. Sample techniques used in this research was purposive sampling. The sample of the research were 14 company agricultural sector and 31 company sector mines in the Indonesia Stock Exchange ( IDX ). Technique analysis the data used was Independent T-Test .The results of the study showed that the company the mining sector and agriculture is at a healthy condition and there is not differences between the mining sector and agricultureKeywords: Grover, Agriculture, Mining, IDX, Independent T-Test